2004
DOI: 10.1016/j.ces.2004.03.042
|View full text |Cite
|
Sign up to set email alerts
|

CFD studies of dynamic gauging

Abstract: Dynamic gauging is a non-contact technique for measuring the thickness of soft deposit layers on solid surfaces immersed in liquid environments, in situ and in real time. The technique works by inducing a flow into a nozzle located close to, and normal to, the deposit surface; the relationship between pressure drop and mass flow rate yields a measure of the distance between the nozzle and the deposit, whence the thickness of the deposit can be deduced. Computational Fluid Dynamics (CFD) studies were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…CFD studies performed by Chew et al (2004a) showed the applicability of an analytical solution for a centripetal flow to compute the shear stress in the gap between nozzle and surface:…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation
“…CFD studies performed by Chew et al (2004a) showed the applicability of an analytical solution for a centripetal flow to compute the shear stress in the gap between nozzle and surface:…”
Section: à3mentioning
confidence: 99%
“…In this study fluid dynamic gauging (FDG) as described by Chew et al (2004a) was used for measuring the mechanical strength (i.e., shearing yield strength or cohesive strength) of biofilms. This method provides the advantage that the forces acting on the biofilm derive from fluid flow tangential to substratum surface.…”
Section: Introductionmentioning
confidence: 99%
“…ms indicates that the flow below the rim of this nozzle design can be solved analytically for steady radial flow between parallel discs. The flow rate can be estimated using the discharge coefficient correlation published by Tuladhar et al (2000), whose accuracy has been confirmed by CFD (Chew et al, 2004a).…”
Section: A Methods For Measuring the Strength Of Scale Deposits On Heamentioning
confidence: 99%
“…the clean condition. For the experiments performed here with Newtonian liquids, the flows lie in the laminar regime so the stresses imposed on the surface can be calculated by numerical solution of the governing Navier-Stokes and continuity equations (see Chew et al 2004a). Ths combination of thickness measurement, in response to imposed stress, yields the deformation behaviour of the fouling layer and has been applied to soft layers of food materials by Chew et al (2004b).…”
Section: Fluid Dynamic Gaugingmentioning
confidence: 99%
“…This value represents the greatest shear stress applied during FDG readings, which occurs at the inner edge of the nozzle rim (a radial distance of dt/2 from the centreline) (Chew et al, 2004). The test section was m ounted in the flow loop shown in Fig.…”
Section: 2mentioning
confidence: 99%